Acute effects of dynamic stretching and post-activation potentiation enhancement warm-up strategies on physical performance and flexibility in elite tennis players - Moreno-Pérez, V.; Hernández-Davó, J. L.; Nakamura, F.; López-Samanes, Á.; Jiménez-Reyes, P.; Fernández-Fernández, J.; Behm, D. G. (Journal of Back and Musculoskeletal Rehabilitation, 2021)
OBJECTIVE: The aim of this study was to compare the potential post-activation performance enhancement (PAPE) effects of two different warm-up strategies, involving dynamic stretching (DS) or heavy load leg press (HL) on several key physical qualities in tennis players. METHODS: Twenty-six elite male tennis players (age: 19.22 ± 4.20 years; body mass: 67.37 ± 8.19 kg; height: 1.77 ± 0.07 m) performed both warm-ups, with 48-hours between protocols (DS and HL), performed in a randomized order. Pre- and post-tests included: countermovement jump, 5-m and 10-m sprint, 5-0-5 agility test, and hip extension and flexion range-of-motion which were performed before and after DS and HL warm-up protocols. RESULTS: The DS warm-up led to substantial improvements in 5-m and 10-m sprint, 5-0-5 agility test, countermovement jump, and also to higher hip flexion range-of-motion. The HL warm-up caused impairments in 5-m and 10-m sprints, but improvements in 5-0-5 agility test, countermovement jump and hip extension range-of-motion. Compared to HL, DS warm-up induced possibly to likely positive effects on 5-m and 10-m linear sprint performance, as well as in hip flexion range-of-motion. Nevertheless, no differences in performance improvements in 5-0-5 agility test, countermovement jump and hip extension range-of-motion were found when comparing DS and HL warm-up protocols. CONCLUSION: DS seems to be more effective than HL when performing a short warm-up protocol in elite tennis players.